Pemberdayaan Mahasiswa PBA UNM Melalui Pendampingan Penyusunan Buku Saku Bahasa Arab Pariwisata Dan Pelatihan Maharah Kalam Berbasis Proyek - Dessy Sintari Daoed; Irfan; Hikmatul Lailaa (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
South Sulawesi, particularly Makassar, is a priority tourist destination with significant potential to attract international tourists from the Middle East (halal tourism). However, the availability of competent Arabic language tour guides is still limited. Students of the Arabic Language Education (PBA) Study Program at Makassar State University (UNM) possess basic linguistic potential, but face challenges in practicing their speaking skills (maharah kalam) in a tourism context due to the lack of specific teaching materials (Arabic for Specific Purposes). This community service program aims to empower students through: (1) Providing practical teaching media in the form of a Pocket Book on Tourism Arabic (Al-Arabiyyah Al-Siyahah), and (2) Improving maharah kalam competency through intensive training using role-playing methods and field practice. The implementation method uses a Participatory Action Learning (PAL) approach, which includes needs analysis, preparation of the pocket book, training workshops, tour guide simulations, and evaluation. The target output of this activity is a Pocket Book product and an increase in students' speaking proficiency scores of at least 75% in the context of hospitality and guiding.